Perkembangan Toleransi dalam Pendidikan Islam di Indonesia - Akhmad Akhmad (SCHOLASTICA: Jurnal Pendidikan dan Kebudayaan, 2020)
The value of tolerance is one of the values ​​that must be done by everyone in life. Tolerance among humans is done to make human diversity a superior value not a differentiating value. In Islamic education tolerance has a very broad meaning so that in studying this value it will provide more value in carrying out social life because the value of tolerance has a very good meaning in human life. The purpose of this study is to see and explain the development of tolerance in Indonesia in Islamic education so that we can see together that in Islam the value of tolerance has more value and is also studied. This study uses a literature study method using various articles, books, journals to support this research. Based on Islamic education in Indonesia, education in the value of tolerance has a value that can overcome the value of intolerance in religion so that the results of this research will increase the value of mutual tolerance according to Indonesian education. The results in this study indicate that in Islamic education, especially tolerance has a concrete meaning in tolerance so that this value can create tolerance for others and religion.